Screens and scars: SEM analysis of the relationship between childhood trauma, emotion regulation, and social media addiction - Nurten Elkin; Ashifa Kariveliparambil Mohammed Ashraf; Oğuzhan Kılınçel; Şenay KılınçeL; Maharshi Ranganathan; Aslıhan Kübra Sakarya; Ayşe Mücella Soydan (Frontiers in Psychology)
BackgroundAddiction is an increasingly significant global public health concern, affecting individuals across diverse age groups and demographics. With the rapid rise of digital technology, social media addiction has emerged as a growing behavioral issue, impacting mental health, interpersonal relationships, and daily functioning.MethodsThis study employed an online cross-sectional self-report questionnaire, with university students aged 16–35 years as the target population. Data were collected using Google Forms questionnaires, accessible via the university registration system, and sent to the participating students’ smart phones. The data collection instruments included the Social Media Addiction Scale (SMAS), the Childhood Trauma Scale (CTS), and the Difficulty in Emotion Regulation Scale (DERS).ResultsData from 318 university students were analyzed. The analysis of sociodemographic data revealed a mean participant age of 21.2 years, with 87.3% being female. An analysis of the relationship between social media addiction and childhood trauma revealed that participants with childhood trauma had higher social media addiction. The linear regression model, including childhood traumas and emotion regulation difficulties for social media addiction scores, was statistically significant. A positive correlation was observed between social media addiction and difficulty in emotion regulation.ConclusionThese findings suggest that individuals who struggle with emotion regulation tend to use social media more frequently. Furthermore, the negative effects of childhood trauma on emotion regulation capabilities during adulthood contribute to the development of social media addiction.